Malnutrition is related to functional impairment in older adults receiving home care - Kiesswetter, Eva; Pohlhausen, S.; Uhlig, K.; Diekmann, Rebecca; Lesser, Stephanie; Heseker, H.; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2013)
The aims of this work were (a) to provide a detailed description of the association between nutritional (Mini Nutritional Assessment; MNAA (R)) and functional status in a sample of older adults receiving home care, using both questionnaire- and performance-based functional methods, and (b) to investigate the impact of different MNA subscales on this association.Multi-centre, cross-sectional.Home care.296 persons a parts per thousand yen65 years in need of care (80.7 +/- 7.7 y).Nutritional status was determined by the MNA and functional status by two questionnaires (Instrumental and Basic Activities of Daily Living; IADL, ADL) and three performance tests (handgrip strength, HGS; Short Physical Performance Battery, SPPB; Timed 'Up and Go' Test, TUG). A categorical and a covariance analytical approach were used to test for differences in functional status between MNA groups (well nourished, risk of malnutrition, malnourished). In addition, functional parameters were correlated with total MNA, a modified MNA version (modMNA), where functional items were excluded, and MNA subscales ('functionality', 'general assessment', 'anthropometry', 'dietary assessment', and 'subjective assessment').57% of the participants were at risk of malnutrition and 12% malnourished. 35% reported severe limitations in IADL, 18% in ADL. 40%, 39% and 35% had severe limitations in HGS, SPPB and TUG; 9%, 28% and 34% were not able to perform the tests. Functional status deteriorated significantly from the well nourished to the malnourished group in all functional measures. The modMNA was weak but still significantly related to all functional parameters except TUG. The subscale 'functionality' revealed strongest correlations with functional measures. All other MNA subscales showed only weak or no associations.More than one half of the seniors receiving home care were at nutritional risk and poor functional level, respectively. Malnutrition according to MNA was significantly associated to both questionnaire- and performance-based functional measures even after exclusion of functional MNA items.
Keywords: Mini Nutritional Assessment; functional status; Activities of Daily Living; performance tests; home care